Effect of Body Condition Score Limousine Crossbred Cow on Cattle Oestrus Response Synchronized using PGF2α Single Dose - Muhammad Zainul Hanif; Putri Utami; Aulia Puspita Anugra Yekti; Asri Nurul Huda; Joko Riyanto; Chusnul Hanim; Mashudi Mashudi; Trinil Susilawati (Buletin Peternakan, 2022)
One  of  the  strategies  to  increase  the  cattle  population  in  Indonesia  is  the  AI (Artificial   Insemination)  method.  The  AI program's  improvement  of   reproductive efficiency can use the oestrus synchronization method. The purpose of this study was to evaluate   the   effect   of   body   weight   and   body   condition   score   on   the   oestrus synchronization  response with  the brand  "lutelyse."  This  research  was  conducted  in  Senggreng  Village,  Sumberpucung  District,  Malang Regency,  This  research  method uses experimental field experiments  with a sampling technique of purposive sampling. This study took a sample of 21, aged 1,5 –5 years, synchronized with PGF2α as much as  5  ml,  which  was  then  carried  out  by  observing  oestrus  behavior  for  24  hours after synchronization.  The  results  showed  that,  the  percentage  of  oestrus in  cows  with body condition  score  (BCS) 4,  which  is  76.92%,  is  lower  than  cows  with  BCS  5,  which  is 100%.  For  the synchronization  distance  with  the  onset  of  oestrus  in  BCS  4  cattle, namely 3802.92 ± 1007.80 (minutes) and BCS 5, namely 4081 ± 884.91 (minutes) with  the results of the conception rate of BCS 4 cattle of 38.46% and BCS 5 of 50%. Based on the results of the study, it was concluded that BCS 5 has a higher success pregnancy rate than BCS 4.